2017
DOI: 10.1515/botcro-2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antifungal potential of medicinal plants against seedborne mycoflora of eggplant (Solanum melongena L.)

Abstract: -Antifungal activities of medicinal plants were observed against seedborne mycofl ora of eggplant (Solanum melongena). The effect of ethanolic leaf extracts of Mangifera indica, Mentha spicata, Citrus limon, Eucalyptus camaldulensis against four isolated fungal species including Fusarium oxysporum, Aspergillus fl avus, Rhizopus stolonifer and Penicillium digitatum was evaluated at various concentrations, by using the poisoned food technique. The impact of the extracts on seed germination and growth of eggplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…(Table 1). Similarly, Aidoo et al, (2011) reported that the Aspergillus is a predominant fungus (21.5 %) followed by Penicillium (17.0%) and similar pattern of incidence was reported by Bhajbhuje (2013), Singh and Sharma (2013) and Ashiq et al, (2017). Such dominance by Aspergillus could be due to competitive inhibition of P. vexans, which could be due to suppression of germination and growth of C. capsici as reported in chilli (Gupta, 2016).…”
Section: Resultsmentioning
confidence: 54%
“…(Table 1). Similarly, Aidoo et al, (2011) reported that the Aspergillus is a predominant fungus (21.5 %) followed by Penicillium (17.0%) and similar pattern of incidence was reported by Bhajbhuje (2013), Singh and Sharma (2013) and Ashiq et al, (2017). Such dominance by Aspergillus could be due to competitive inhibition of P. vexans, which could be due to suppression of germination and growth of C. capsici as reported in chilli (Gupta, 2016).…”
Section: Resultsmentioning
confidence: 54%
“…Once it enters the body of a feeding insect, it destroys its nervous system, ultimately resulting in changes in its feeding behaviour, followed by paralysis and death. As another approach to viral disease management, many medicinal plants possess antimicrobial properties (Nashwa and Abo-Elyousr, 2012;Ashiq et al, 2017) and are applied to control fungal, bacterial, and viral diseases of diverse economically important crops. Additionally, use of plant extracts and soft soap solutions can control most of the important sucking and chewing insects including whiteflies, aphids, thrips, leafminers, armyworm, and small beetles (Elwell and Maas, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants contain large number of secondary phytomedicines like phenols, flavonoids, alkaloids, saponins, tannins, steroids etc. possesses synergistic effects used for remedial purposes [4]. These secondary bioactive compounds have different structures with different mode of action used to control microbial growth and survival.…”
Section: Introductionmentioning
confidence: 99%